Managing Islamic-Characteristic Elementary Schools: A Qualitative Study of School Governance, Curriculum, Teachers, Facilities, and Financing in Serang City - Hermansah Hermansah; Fadlullah Fadlullah; Yuyu Yuhana (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study is motivated by the importance of managing Islamic elementary schools as an effort to improve educational quality comprehensively while maintaining strong Islamic values. The research aims to analyze the management dynamics of five Islamic elementary schools in Serang City, focusing on their curriculum, teacher management, facilities and infrastructure, and school financing. A qualitative approach with a grounded research design was employed in this study. The research sites included SD Islam Al-Azhar, SDIT Al-Izzah, SD Persis, SD Islam Tirtayasa, and SD Muhammadiyah Serang City. Data were collected from principals, teachers, and school committee members through interviews, observations, and document analysis, and were subsequently analyzed using the Miles and Huberman model. The findings reveal that all schools integrate Islamic values into curriculum implementation, teacher management, facility administration, and financial management. However, each school demonstrates a distinct institutional identity, reflected in the educational models adopted by SD Islam Al-Azhar, SDIT Al-Izzah, SD Persis, SD Islam Tirtayasa, and SD Muhammadiyah. These differences are evident in curriculum integration patterns, teacher professional development programs, facility management, financing strategies, and school branding. The researcher concludes that school management at SD Islam Al-Azhar, SDIT Al-Izzah, SD Persis, SD Islam Tirtayasa, and SD Muhammadiyah is implemented in a structured, participatory, and collaborative manner, grounded in Islamic values. This research contributes to the development of Islamic educational management studies, particularly in understanding value-based governance of Islamic elementary schools as a foundation for enhancing quality and institutional sustainability.